Increased Macular Pigment Optical Density and Visual Acuity following Consumption of a Buttermilk Drink Containing Lutein-Enriched Egg Yolks: A Randomized, Double-Blind, Placebo-Controlled Trial - Sanne M. van der Made; Elton R. Kelly; Aize Kijlstra; Jogchum Plat; Tos T. J. M. Berendschot (Journal of Ophthalmology)
Purpose. To study the effect of 1-year daily consumption of a dairy drink containing lutein-enriched egg yolks on macular pigment optical density (MPOD) and visual function parameters in elderly subjects with ocular drusen and/or retinal pigment abnormalities. Methods. One hundred and one subjects were recruited to participate in this randomized, double-blind, placebo-controlled parallel intervention trial. Statistical analyses were performed with 46 subjects in the lutein group and 43 in the control group. MPOD, best corrected visual acuity (BCVA, logMAR), and dark adaptation were measured at the start of the study, after 6 months and after 12 months. Plasma lutein and zeaxanthin concentrations were assessed at baseline and at the end of the study. Results. In the lutein group, plasma lutein concentrations increased significantly from 205 ng/mL at baseline to 399 ng/mL after twelve months of intervention. MPOD increased significantly from 0.45 to 0.52 and BCVA improved significantly from −0.04 to −0.09 LogMar. Differences in rod dark adaptation rate between both groups were not significant. Conclusion. Daily consumption of a dairy drink containing lutein-enriched egg yolks for one year improves visual acuity, MPOD, and plasma lutein concentration in elderly subjects with drusen and/or retinal pigment epithelial abnormalities.